2016
DOI: 10.1021/acsinfecdis.6b00006
|View full text |Cite|
|
Sign up to set email alerts
|

Immunodominant SARS Coronavirus Epitopes in Humans Elicited both Enhancing and Neutralizing Effects on Infection in Non-human Primates

Abstract: Severe acute respiratory syndrome (SARS) is caused by a coronavirus (SARS-CoV) and has the potential to threaten global public health and socioeconomic stability. Evidence of antibody-dependent enhancement (ADE) of SARS-CoV infection in vitro and in non-human primates clouds the prospects for a safe vaccine. Using antibodies from SARS patients, we identified and characterized SARS-CoV B-cell peptide epitopes with disparate functions. In rhesus macaques, the spike glycoprotein peptides S471-503, S604-625, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
362
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(374 citation statements)
references
References 50 publications
6
362
1
5
Order By: Relevance
“…Five regions contain epitopes recognized by neutralizing antibodies in SARS convalescent sera (Guo et al, 2004;Shichijo et al, 2004). Among those, of particular interest is the 587-628 region nesting the 604À625 peptide, which was identified in a SARS convalescent patient and found to have the capacity to elicit antibodies that efficiently prevent infection in non-human primates (Hu et al, 2005;Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Five regions contain epitopes recognized by neutralizing antibodies in SARS convalescent sera (Guo et al, 2004;Shichijo et al, 2004). Among those, of particular interest is the 587-628 region nesting the 604À625 peptide, which was identified in a SARS convalescent patient and found to have the capacity to elicit antibodies that efficiently prevent infection in non-human primates (Hu et al, 2005;Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, serum from deceased patients -but not SARS survivors during early stages of infection -enhanced IL-6, IL-8, and MCP1 production by wound-healing macrophages (Figure 8). We previously identified epitopes in S protein that elicited NAbs and antibodies that enhanced SARS-CoV infection (48,49). Further studies that will attempt to identify antibodies and epitopes that mediate prevention or enhancement of ALI might be needed for future vaccine design and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present a comprehensive immunogenicity map of the SARS-CoV-2 virus (Table S1), highlighting 65 B and T cell epitopes (Tables 1, S1 and S2) from a diverse sampling of viral domains across all 9 SARS-CoV-2 genes. Based on our computational algorithm, we expect that the highest scoring peptides will result in safe and immunogenic T cell epitopes, and that B cell epitopes should be evaluated for safety and efficacy using methods previously reported (Wang et al, 2016). mRNA vaccines have been shown to be safe and effective in preclinical studies (Richner et al, 2017), with nucleoside RNAs shown to be effective without triggering RNA-induced immunogenicity (Pardi et al, 2017), while DNA vaccines have also been shown to be safe and protective (Dowd et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid deployment of antibody-based vaccination against SARS-CoV-2 raises a major concern in accelerating infectivity through Antibody-Dependent Enhancement (ADE), the facilitation of viral entry into host cells mediated by subneutralizing antibodies (those capable of binding viral particles, but not neutralizing them) (Dejnirattisai et al, 2016). ADE mechanisms have been described with other members of the Coronaviridae family (Wan et al, 2020;Wang et al, 2016), and it has already been suggested that some of the heterogeneity in COVID-19 cases may be due to ADE from prior infection from other viruses in the coronavirus family (Tetro, 2020). We suggest that although the T cell epitopes presented here are expected to be safe in vaccination, B cell epitopes should be further evaluated for their ability to induce neutralizing antibodies as compared to their potential to induce ADE.…”
Section: Introductionmentioning
confidence: 99%